Analysis of the population structure and physiological status differences of yangtze finless porpoises (Neophocaena asiaeorientalis) across habitats in Poyang lake - Yi Huang; Heng Yin; Lingxia Wei; Yun Zhang; Rongcheng Rao; Ying Yang; Fangning Liu; Jialing Min; Jinxiang Yu; Jianglong Que (PLoS ONE, 2026)
To investigate the physiological status of Yangtze finless porpoises (YFPs) in Poyang Lake and assess health conditions across different habitats at a mesoscale geographical level, physical examination data from 25 individuals were collected from two habitats: Piaotou (PT, 19 individuals), Jinxi Lake (JX, 6 individuals). Independent samples t-test and Mann-Whitney U test were used to compare blood parameters between PT and JX population. Robust M-estimation was applied to conduct stratified tests on the independent effects of factors. Robust PCA was used to characterize the overall physiological differences between the two habitats. Using the ranges of healthy YFPs blood parameters as the reference group, Games-Howell test was used for multiple group comparisons. Results revealed significant differences in physiological status between YFPs inhabiting Piaotou and Jinxi Lake. Piaotou population exhibit better physiological status, characterized by higher oxygen-carrying capacity, nutritional status, and metabolic activity levels, while those in Jinxi Lake showed enhanced coagulation function or inflammatory responses. In hematological parameters, the PT population showed significantly higher red blood cell-related indices than the JX's. The JX population exhibited higher platelet-related parameters and extremely low Eosinophil counts and percentages. More parameters in the JX population differed significantly from the range of healthy physiological indicators, with Monocyte count and percentage, and Plateletcrit exceeding normal physiological ranges. For blood biochemical parameters, Aspartate amino Transferase and Triglyceride in the PT population, and Alkaline Phosphatase and Triglyceride in the JX population exceeded reference ranges. This study revealed significant physiological differences among YFPs inhabiting different habitats within the same lake system, indicating that the Piaotou population can serve as high-quality germplasm resources, while the Jinxi Lake population shows certain health risks in their physiological status.